LOGAM-LOGAM BERAT PENCEMAR LINGKUNGAN DAN EFEK TERHADAP MANUSIA - Endrinaldi Endrinaldi (Faculty of Public Health, Andalas University, 2009)
Heavy metals are the hazardous substance that produced by industrial waste, included arsenic (As), lead (Pb), mercury (Hg) and cadmium (Cd). That heavy metal could cause acute and chronic body intoxication. Health effects of heavy metal intoxication such as nervous system, kidney, liver, bone, respiratory system, reproductive system, hematopoietic system, cardiovascular, gastrointestinal tract disorders. The manifestation of the toxic effect in tissue and organ is caused by interaction between heavy metal and important cell molecules thus destruct the structure and the function of the cell at the target organ.